The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1016/j.euroecorev.2008.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Inflation, price dispersion, and market structure

Abstract: Abstract. In this paper, we use a unique micro-level data set from Istanbul to investigate the empirical relationship between inflation and price dispersion. In particular, our data set includes price observations from three distinct store types: bakkals (convenience stores), pazars (bazaars), and supermarkets. Our findings indicate that pazars exhibit the least amount of price dispersion on average, which is consistent with the fact that menu and search costs are very low in the pazar and that such sellers se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…High levels of price dispersion motivate buyers to execute more search activities and examine differences among alternatives in order to locate the most suitable product. Previous studies have found the positive effect of price dispersion on search intention (Biswas & Burman, 2009;Caglayan et al, 2008). As buyers spend more time and effort on the transaction, the cost of transaction increases and the perceived value decreases.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…High levels of price dispersion motivate buyers to execute more search activities and examine differences among alternatives in order to locate the most suitable product. Previous studies have found the positive effect of price dispersion on search intention (Biswas & Burman, 2009;Caglayan et al, 2008). As buyers spend more time and effort on the transaction, the cost of transaction increases and the perceived value decreases.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Caglayan and Filiztekin (2006) estimate that nominal prices stay for 3 months on average, using data from Istanbul Chamber of Commerce for the calculation of a cost of living index for wage earners in Istanbul. Caglayan et al (2008) show that the mean price duration depends on the market structure. While these results are similar to our findings, their data falls short of consumer price coverage (around 25% of the cost of living index).…”
Section: Overview Of Inflation In Turkeymentioning
confidence: 99%
“…Furthermore, this result is robust to different time periods as Table 5 shows. 9 Moreover, inflation expectations and uncertainty can be the underlying causes behind this kind of relation (see, for example, Caraballo et al 2006, Caraballo and Dabús 2008, Caglayan et al 2008, Becker and Nautz 2009band Choi 2010. This issue is studied in the next section.…”
Section: [Table 5 Here]mentioning
confidence: 99%